(untitled) (Encuentros, 2020)
The following text presents various comments and personal reflections about the article written by our colleague and compatriot N. Quintas-Froufe in mid-2016, a document which was published in the prestigious colombian journal Palabra Clave in January 2018. As a Spanish researcher and connoisseur of the television field of my country, I would like to make some concise assessments about the content of the aforementioned scientific text; concluding that the decline of Spanish public television is a trend that began in the late twentieth century, with the appearance of private television, and increased with new forms of information consumption.